Pendidikan Rabbani dalam Al-Qur’an - Yayat Suharyat; Abdul Ghofur; Amiruddin Abdullah (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2022)
The Qur'an is the Kalamullah which is the guide of life for humans. One of the important themes raised in the discussion of the Qur'an is education. Education in the Qur'an ultimately produces human beings with divine character (Rabbani). The word Rabbani is repeated at least three times in the Qur'an which means Al-Tarbiyah. This study is a literature review using a descriptive qualitative research approach, namely a research approach that seeks to describe a symptom of an ongoing event, in other words this descriptive research is research that takes a problem or focuses attention on actual problems as they were at the time of the research. carried out with reference to primary and secondary sources relevant to this study. Education in the perspective of the Qur'an has the goal that humans have faith and piety to Allah and His Messenger, besides that to build good morals in society through social activities so that by nature the goal of human creation is truly achieved, namely to become khalifatullah on earth. Among the characteristics of humans who have achieved the title of caliph are those who have been able to actualize all of their human potential, so that their usefulness is truly recognized in society.